Relationship between long non-coding RNA and prognosis of patients with coronary heart disease after percutaneous coronary intervention: A protocol for systematic review and meta-analysis - Wang, Fei (Medicine (Baltimore), 2020)
BACKGROUND: Long non-coding RNA (lncRNA) can predict the prognosis of patients with coronary heart disease (CHD) after obtaining percutaneous coronary intervention (PCI), while this conclusion still needs to be further confirmed. Therefore, this study attempted to explore the relationship between lncRNA and prognosis in CHD patients after PCI. METHODS: The database was retrieved from China National Knowledge Infrastructure (CNKI), Chinese Biomedical literature Database (CBM), Chinese Scientific and Journal Database (VIP), Wan Fang database, PubMed, and EMBASE. Hazard ratios (HRs) and its 95% confidence interval (CIs) were applied to assess the prognostic effects of lncRNA on overall survival (OS). RevMan 5.3 and STATA 16.0 software were used to perform meta-analysis. RESULTS: The results of this meta-analysis would be submitted to peer-reviewed journals for publication. CONCLUSION: This review provided a comprehensive overview of the relationship between lncRNA and prognosis in CHD patients after PCI, and offered recommendations for clinical practices or guidelines.